Chronic Patellar Dislocation Treated With Extensive Lateral Release and Vastus Medialis Obliquus Advancement: A Case Report - Shayne R. Kelly; Adam V. Daniel; Patrick A. Smith (Case Reports in Orthopedics)
The following case report demonstrates a case of a chronic irreducible patellar dislocation, age-indeterminate associated with a large medial patellar avulsion fracture that was treated with a vastus medialis obliquus advancement following an extensive lateral release. This case is the only known report of this kind in the literature. The patient is a 41-year-old Caucasian female who presented to the clinic with an age-indeterminate, chronically dislocated patella. She has a past medical history of hypertension and ischemic stroke 1 year prior to presentation, leading to expressive aphasia and lower extremity weakness in addition to patellar instability dating back to age 13. An unsuccessful patellofemoral reduction was performed at an outside clinic, and she was placed in a knee immobilizer and referred to our office. Clinically, the patient had limited knee range of motion with a fixed lateral patellar dislocation that was confirmed on imaging. This case report demonstrates a surgical reduction technique that can be utilized by orthopedic surgeons for chronic patellar dislocations that are not amenable to routine patellar instability surgeries due to the contraction of surrounding soft tissue, chronic bone abnormalities, and position of the chronic dislocation. An extensive lateral release followed by vastus medialis obliquus advancement was performed to center the patella within the trochlear groove and to allow for stable articulation throughout range of motion. The patient was able to regain painless, full range of motion of her knee postoperatively with patellar stability noted on both physical exam and radiographic imaging.